2023
DOI: 10.1093/ageing/afad015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of study factors in the association of periodontal disease and cognitive disorders: systematic review and meta-analysis

Abstract: Aim The aim was to assess study factors that impact the association of cognitive disorders in people with periodontal disease (PD). Method Medline, EMBASE and Cochrane databases were searched until February 2022 using keywords and MeSH: (periodon* OR tooth loss OR missing teeth) AND (dementia OR Alzheimer’s Disease OR cognitive*). Observational studies reporting prevalence or risk of cognitive decline, dementia or Alzheimer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Data from a recent national US retrospective cohort study showed that periodontal pathogens increase the risk of AD incidence and mortality [143]. In addition, data from a recent meta-analysis showed that the risk of cognitive disorder in individuals with PeD increases as the severity of PeD increases, and this risk appears to be greater in the female sex [144]. There are at least two main mechanisms by which PeD can cause cognitive disorders.…”
Section: Chronic Low-grade Inflammation and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from a recent national US retrospective cohort study showed that periodontal pathogens increase the risk of AD incidence and mortality [143]. In addition, data from a recent meta-analysis showed that the risk of cognitive disorder in individuals with PeD increases as the severity of PeD increases, and this risk appears to be greater in the female sex [144]. There are at least two main mechanisms by which PeD can cause cognitive disorders.…”
Section: Chronic Low-grade Inflammation and Neurodegenerative Diseasesmentioning
confidence: 99%
“…There are at least two main mechanisms by which PeD can cause cognitive disorders. The first involves the presence of an increased cerebral inflammatory state caused by the SCI process originating from oral pathogens; the second involves a direct action of periodontal bacteria on the CNS that cross the BBB and cause its breakdown with subsequent, potential triggering of the preexisting neurodegenerative process [141][142][143][144].…”
Section: Chronic Low-grade Inflammation and Neurodegenerative Diseasesmentioning
confidence: 99%
“…And the other is suboptimal oral health, such as gingivitis, dental caries, tooth loss, and edentulousness, appears to be associated with increased risk of developing cognitive impairment and dementia. In recent meta-analysis about the relationship between periodontal disease and cognitive disorder, risk of cognitive decline in increased with periodontal disease severity [40] . The other meta-analysis [12] showed that there are three possible mechanisms by which tooth loss leads to cognitive decline: tooth loss may reduce sensory stimulation to the brain, dental status can be linked to cognitive impairment via the nutritional pathway, and periodontal disease may play a role through neuro-inflammation.…”
Section: Oral Health and Cognitive Impairment/dementiamentioning
confidence: 99%
“…Previous studies reported that poor cognitive function also leads to poor oral health among older adults 10–12 . A previous longitudinal study showed that the association between cognitive function and oral health was bidirectional 13 .…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies reported that poor cognitive function also leads to poor oral health among older adults. [10][11][12] A previous longitudinal study showed that the association between cognitive function and oral health was bidirectional. 13 Therefore, a bidirectional association could exist between poor oral health and poor cognitive function, which in turn leads to poor oral health.…”
Section: Introductionmentioning
confidence: 99%